Environment and chronic disease in rural areas of Heilongjiang, China (ECDRAHC). Issue 1 (17th January 2023) - Jiang, Yuting; Feng, Hongqi; Jiao, Zhe; Du, Yang; Li, Yuanyuan; Liu, Xiaona; Tong, Simeng; Shao, Xinhua; Li, BingYun; Sun, Hongna; Meng, Fangang; Shen, Yuncheng; et al.
Abstract : Purpose: Environmental factors such as long-term exposure to cold can increase the risk of chronic diseases. However, few studies have focused on the impact of environmental factors and lifestyle changes on chronic diseases. To fully explore the association between exposure to environmental factors and the prevalent risk of various chronic diseases, we conducted a large cohort study (Environment and Chronic Disease in Rural Areas of Heilongjiang, China (ECDRAHC)). The ECDRAHC collected detailed questionnaire data covering 10 sections, physical measurements and blood and urine samples. In this study, we describe the design and implementation of the cohort study and present the findings for the first 10 000 participants. Participants: The ECDRAHC study was carried out in rural areas where the annual average temperature is 2.9°C, and aimed to recruit 40 000 participants who are long-term residents aged 35–74 years. The participants will be followed up every 5 years. Currently, ECDRAHC has reached 26.7% (n=10 694) of the targeted population. Findings to date: A total of 10 694 adults aged 35–74 years were recruited, including 61.7% women. The prevalence of current smokers was 46.8% in men and 35.4% in women. The mean blood pressure was 140.2/89.9 mm Hg and 135.7/85.0 mm Hg in men and women, respectively. The mean body mass index was 24.74 kg/m 2 in men and 24.65 kg/m 2 in women, with >7.3% being obese (>30 kg/m 2 ). The main non-communicable diseases found in phase 1 were hypertension, diabetes, hypertriglyceridaemia and metabolic syndrome, with a higher prevalence of 51.0%, 21.6%, 46.8% and 42.6%, respectively. Future plans: We plan to complete the follow-up for the first phase of the ECDRAHC in 2024. The second and third phase of the cohort will be carried out steadily, as planned. This cohort will be used to investigate the relationship between environmental factors, lifestyle, and genetic and common chronic diseases.